Rational Design of Ni‐Based Electrocatalysts by Modulation of Iron Ions and Carbon Nanotubes for Enhanced Oxygen Evolution Reaction. (16th November 2020) - Song, Daqi; Wang, Liang; Yao, Mengyao; Sun, Weiwei; Vajtai, Robert; Ajayan, Pulickel M.; Wang, Yong
Abstract: Although Ni‐based compounds perform well as oxygen evolution reaction (OER) catalysts, several challenges hinder their potential applications, namely, complicated synthesis and pyrolysis, poor conductivity, and poor stability. Herein, a facile large‐scale synthesis strategy is designed for unique Fe‐doped Ni‐based metal‐organic polymer@carbon nanotubes (CNTs) composites that may be used as OER electrocatalysts without further treatment. The Ni1.95 Fe‐MOP@CNTs deliver a small overpotential of 256 mV to achieve a current density of 10 mA cm −2, and their Tafel slope is low to 58 mV dec −1 . In addition, the catalyst displays high durability after a long‐term test of 60 000 s. Introducing Fe ions and CNTs into Ni‐based compounds increases the surface area and enhances the degree of graphitization and the composite conductivity, contributing to the excellent catalytic performance. The charge transfer reaction dynamics are explored using in situ differential electrochemical mass spectrometry. Surprisingly, the Ni1.95 Fe‐MOP@CNTs demonstrate a Faraday efficiency of (≈92.7%) for O2 production. These findings pave a new way for synthesizing catalysts without post‐processing for water oxidation. Abstract : A novel Fe doped Ni‐based metal‐organic‐polymer@carbon nanotubes (CNTs) composite is synthesized by a facile hydrothermal method. The introduction of both Fe ions and CNTs into the Ni‐based compounds increases the surface areas and enhances the degree of graphitization and the composite conductivity, which gives this material excellent oxygen evolution reaction performance.